A Historical Review of the Development of the Islamic Banking System (An Analytical Study) - Alafianta, Novan Fatchu; Aziz, Muhammad Abdul; Sahputra, Jaya (AL- IKTISAB Journal of Islamic Economic Law, 2021)
This paper tries to investigate the historical development of Islamic banking in the world. The formation of Islamic banking was inspired by the incompatibility between conventional banks and Islamic teachings based on the Qur'an and al-Hadith. Islamic economists are trying to replace and improve the traditional system of banking that has developed rapidly with the Islamic banking system. The establishment of Mit Ghamr marked the emergence of Islamic banking. Since then, many Islamic banks have been established and have proliferated. The primary purpose of this study is to analyze and determine the historical development of the Islamic banking system in various countries. Thus, this research can provide further information for Muslim economic actors as a guide in carrying out economic activities, especially those related to banking. This study using the historical analysis method and at the end of this paper, confirm that the Islamic banking system was preceded by applying a profit-sharing approach to avoid interest in banking. The development of Islamic banks cannot be separated from the efforts made by the Organization of the Islamic Conference (OIC), which since 1970 has issued many recommendations and encouraged its member countries to improve the people's economy in their respective countries. Then, Islamic banks developed in various countries, including Pakistan, Egypt, Iran, Cyprus, Kuwait, Bahrain, United Arab Emirates, Malaysia, Turkey, and Indonesia.